Influence of Resonant Circuits on Optimal Design of Magnetostrictive Energy Harvester in Free Vibration - Mizukawa, Yoshito; Ranta, Jesse; Ahmed, Umair; Blazevic, David; Rasilo, Paavo (IEEE transactions on magnetics, 2024)
This article presents a novel modeling method for a magnetostrictive energy harvester connected to a resonant circuit. The method is based on analytical calculations coupled with experimental parameter identifications. The magnetic flux leakages from the pickup coil and the magnetostrictive material are considered. Under the assumptions of linearity and fundamental oscillation, the governing equations of the magnetostrictive energy harvester were derived from the Euler-Lagrange equations for an electromagnetic-mechanically coupled system. The energy-harvesting efficiency of the harvester was obtained by solving the derived governing equations, and it can be described with five non-dimensional parameters. Among the non-dimensional parameters, the natural frequency ratio and damping ratio of the load resistance have optimal values to maximize the energy-harvesting efficiency. This study derived these optimal design parameters depending on the circuit configuration and types of energy given to the harvester. In the magnetostrictive energy harvester with a series-resonant circuit subject to kinetic energy impact, these optimal design parameters can be obtained in simple algebraic forms. Experimental validations were conducted for the magnetostrictive energy harvester with a pure resistive circuit, with series- and parallel-resonant circuits, respectively, to compare their energy-harvesting efficiencies. While the pure resistive configuration can harvest 21% of given mechanical energy, both series- and parallel-resonant configurations can harvest 23%.